Fanari Hill in the Urban Plan of Hellenistic and Early Roman Nea Paphos and the Question of the ‘Two Akropoleis’ of Nea Paphos - Młynarczyk, Jolanta (Études et Travaux, 2022)
The topography of ancient Nea Paphos features two hillocks, Fabrika and Fanari, that would provide a natural setting for buildings of some significance in the city’s life. Recent discoveries at Fabrika have identified its southern part as a sacred area of the Hellenistic and early Roman period. In contrast, Fanari hill remains virtually unexplored while there are reasons to believe that, beside housing another temple, it was the seat of the civil/military power of the Ptolemies. The aim of this paper is to re-examine all topographical and archaeological evidence related to the Fanari site and its role in the life of Nea Paphos.